[Rezension von: Collins, Kathleen, Politicizing Islam in Central Asia : from the Russian Revolution to the Afghan and Syrian jihads] - Tasar, Eren (A journal of church and state, 2024)
Unusually for a work of political science, this ambitious book aspires to be a work of history. Its author, Kathleen Collins, has indeed assembled historic